The Effect Of Ergonomic And Physical Work Environment Factors On Musculoskeletal Disorders (Msds) In Batik Craftsmen In Danau Teluk District - Devani; Budi Aswin Sanrus; Andree Aulia Rahmat; Muhammad Syukri (CV. AFDIFAL MAJU BERKAH, 2026)
Musculoskeletal disorders (MSDs) are disorders of the muscular and skeletal systems commonly experienced by workers due to unergonomic work postures, repetitive movements, long work durations, and unsupportive physical work environments. Batik artisans are among the workers at risk of developing MSDs because batik-making activities are static, repetitive, and performed over long periods. This study aims to determine the influence of ergonomic and physical work environment factors on musculoskeletal disorders (MSDs) among batik artisans in Danau Teluk District. This study used a quantitative method with an observational analytical cross-sectional design. The study was conducted among batik artisans in Danau Teluk District, Jambi City, with a sample of 40 respondents using a total sampling technique. Data were collected through interviews, observations, temperature and lighting measurements, and assessment of work posture using the Rapid Upper Limb Assessment (RULA) method and MSD complaints using the Nordic Body Map (NBM). Data were analyzed using the Chi-Square test and logistic regression at a 95% confidence interval. The study showed that 17 respondents (42.5%) experienced high-grade MSDs. There was a relationship between work posture (p-value = 0.001), work duration (p-value = 0.000), repetitive motion (p-value = 0.000), and lighting (p-value = 0.000) and the incidence of MSDs. Meanwhile, temperature had no relationship with the incidence of MSDs (p-value = 0.131). The results of the multivariate analysis showed that work posture was the most influential factor on the incidence of MSDs with a p-value = 0.006 and Exp(B) = 64.000. Ergonomic and physical work environment factors influence the incidence of Musculoskeletal Disorders (MSDs) among batik artisans in Danau Teluk District. Work posture is the dominant factor influencing the incidence of MSDs in batik artisans.